A self-template approach to synthesize multicore–shell Bi@N-doped carbon nanosheets with interior void space for high-rate and ultrastable potassium storage. Issue 16 (14th April 2020) - Shi, Xiuling; Zhang, Jianshuo; Yao, Qianqian; Wang, Rui; Wu, Hefeng; Zhao, Yi; Guan, Lunhui
Abstract : Multicore–shell Bi@N–C nanosheets enable high-rate and ultrastable K + storage. Abstract : Metallic bismuth (Bi) is a promising anode for potassium ion batteries (PIBs) due to its high theoretical capacity. However, the large volume fluctuation of the Bi anode results in structural degradation and poor cycling performance. To address these issues, a multicore–shell Bi@N-doped carbon (Bi@N–C) structure, in which Bi nanoparticles are embedded into carbon nanosheets with large interior void room, is synthesized through a facile self-template method. As a PIB anode, the Bi@N–C composite presents highly reversible alloying/dealloying processes, delivering a high capacity of 356 mA h g −1 after 100 cycles at 1 A g −1 . Remarkably, it displays superior rate capability of 266 mA h g −1 at 20 A g −1, and a long lifespan up to 1000 cycles at 10 A g −1 . The kinetics analysis and ex situ characterization experiments disclose that the Bi@N–C electrode shows rapid electron/ion transportation, superior pseudocapacitance behavior, and excellent structural stability during cycles, thus accounting for its excellent electrochemical performance.